Reaction of amorphous/crystalline SiOC/Fe interfaces by thermal annealing. (15th August 2017) - Su, Qing; Zhernenkov, Mikhail; Ding, Hepeng; Price, Lloyd; Haskel, Daniel; Watkins, Erik Benjamin; Majewski, Jaroslaw; Shao, Lin; Demkowicz, Michael J.; Nastasi, Michael
Abstract: The development of revolutionary new alloys and composites is crucial to meeting materials requirements for next generation nuclear reactors. The newly developed amorphous silicon oxycarbide (SiOC) and crystalline Fe composite system has shown radiation tolerance over a wide range of temperatures. To advance understanding of this new composite, we investigate the structure and thermal stability of the interface between amorphous SiOC and crystalline Fe by combining various experimental techniques and simulation methods. We show that the SiOC/Fe interface is thermally stable up to at least 400 °C. When the annealing temperature reaches 600 °C, an intermixed region forms at this interface. This region appears to be a crystalline phase that forms an incoherent interface with the Fe layer. Density functional theory (DFT) Molecular dynamics (MD) is performed on the homogeneous SiFeOC phase to study the early stages of formation of the intermixed layer. Both experimental and simulation results suggest this phase has the fayalite crystal structure. The physical processes involved in the formation of the intermixed region are discussed. Graphical abstract: Structure of amorphous/crystalline interfaces in SiOC/Fe nanocomposites. Image